Preparation method of high-interface-strength DLC (Diamond Like Carbon) coating
By using AIP to deposit interface reinforcement and transition layers in DLC coating, combined with PECVD technology, the problem of insufficient interface bonding strength is solved, and DLC coating with high hardness and low friction coefficient is achieved, improving the wear resistance of the coating Sex and service life.
Patent Information
- Application Number
- CN202411401784.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-14
AI Technical Summary
During use, the existing DLC coatings have insufficient interface bonding strength, which leads to the coating being easily peeled off and falling off, and the hardness and wear resistance cannot meet the requirements.
The interface reinforcement layer and transition layer were deposited using AIP method, and then the hydrogen-containing DLC coating was deposited using PECVD method to ensure that the coating improved hardness and wear resistance while maintaining a dense structure and low friction coefficient.
The high interface bonding strength, high hardness and low surface friction coefficient of DLC coatings are achieved, extending the service life of the coating and directly implementing complex modifications on existing equipment.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a method for preparing a DLC coating with high interface strength. Background Art
[0002] The hard coating prepared by arc ion plating (AIP) technology has been widely used in the surface treatment of tools and molds because of its high hardness, high wear resistance, high toughness and impact resistance. In recent years, as the processing requirements have gradually increased, people have begun to further use multi-arc ion plating technology to prepare hydrogen-free diamond-like carbon (hydrogen-free DLC) coatings using graphite C targets. The main component of this coating is carbon, which is composed of graphite phase and diamond phase. The diamond phase has high hardness and wear resistance, and the graphite phase has good lubrication properties. By reasonably adjusting the ratio of graphite phase to diamond phase, it is possible to obtain a lower surface friction coefficient while ensuring that the coating has a high hardness, which is often less than 0.2, thereby improving the service life of the tool and mold.
[0003] However, due to ion bombardment, particle deposition, and growth defects during the deposition of the DLC coating, the DLC film may have defects such as pinholes, cracks, droplet particles, and weak interface bonding points. The corrosion, wear, and high temperature harsh conditions that exist during use can easily invade the substrate through these defects, causing the DLC coating to fail quickly or fail to function properly. The plasma-assisted chemical vapor deposition (PECVD) method can be used to obtain a DLC film with a dense structure and a lower friction coefficient, which can better avoid the above defects. However, the DLC coating deposited directly on the substrate surface using the PECVD method often has a low hardness and the wear resistance cannot meet the use requirements. Therefore, people try to combine the PVD method with the PECVD method in the hope of obtaining a DLC coating that has both high hardness and wear resistance and a low friction coefficient. For this type of coating, the PVD method used in the existing technical methods is mainly magnetron sputtering, the purpose of which is to minimize the stress of the coating, but its hardness and wear resistance are often insufficient. The main problem with the composite method of AIP and PECVD is that the interface bonding strength of the coating is insufficient, and the coating is very easy to peel off during use.
[0004] Therefore, it is necessary to find an effective method for preparing DLC coating by combining AIP and PECVD to ensure that the coating has high hardness, high wear resistance, high lubricity and good interface bonding strength. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a method for preparing a DLC coating with high interface strength. Compared with the prior art, the present invention adopts AIP (arc ion plating) to complete the deposition of the interface strengthening layer and the transition layer, and then adopts PECVD to deposit the hydrogen-containing DLC coating, which mainly solves the problem of insufficient hardness and wear resistance of the DLC coating prepared by the existing PECVD method, and at the same time maintains the advantages of the DLC coating having a dense surface structure and high lubricity.
[0006] Specifically, the first aspect of the present invention provides a method for preparing a DLC coating with high interface strength, the method comprising the following steps:
[0007] (1) Polishing and cleaning of substrate surface;
[0008] (2) substrate heating and decontamination;
[0009] (3) depositing a metal primer layer on the surface of the substrate, and depositing a carbon transition layer on the metal primer layer;
[0010] (4) depositing an AIP layer on the carbon transition layer;
[0011] (5) depositing a PECVD layer on the AIP layer;
[0012] (6) Cooling to obtain a DLC coating with high interface strength.
[0013] In one embodiment, the specific process of step (1) is: polishing the surface of the substrate to a mirror surface, and then ultrasonically cleaning it with acetone and anhydrous ethanol in sequence.
[0014] In one embodiment, the specific process of step (2) is: at a vacuum degree of 2×10 -2 ~7×10 -2 Pa, the temperature was 100-150℃, argon gas was introduced at a flow rate of 60-100 sccm, and the vacuum degree was maintained at 3×10 -2 ~5×10 - 2 Pa, set the bias voltage between 50 and 900 V, increase gradually or in steps, clean and decontaminate.
[0015] In one embodiment, the specific process of depositing the metal primer layer on the substrate surface in step (3) is as follows:
[0016] S1. Introduce argon gas at a flow rate of 60 to 100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the Cr target, set the arc current to 60A-100A, the bias voltage to 400V-900V, and the deposition thickness to 30-50nm;
[0017] S2. The vacuum is maintained at 3×10 -2 ~5×10 -2 Pa, open the Cr target, set the arc current to 60A-150A, the bias voltage to 40V-400V, and the deposition thickness to 300-800nm;
[0018] S3. Introduce argon gas at a flow rate of 60 to 100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the Cr target, set the arc current to 60A~100A, the bias voltage to 400V~900V, and the deposition thickness to 30~50nm.
[0019] In one embodiment, the specific process of depositing the carbon transition layer on the metal base layer in step (3) is as follows:
[0020] S4. Introduce argon gas at a flow rate of 60 to 100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, turn on the C target, set the arc current to 60A~100A, the bias voltage to 300V~900V, and the deposition thickness to 30~50nm.
[0021] In one embodiment, the specific process of depositing the AIP layer on the carbon transition layer in step (4) is:
[0022] S5. Introduce argon gas at a flow rate of 60 to 100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the C target, set the arc current to 60A-100A, the bias voltage to 200V-400V, and the deposition thickness to 100-500nm;
[0023] S6. Introduce argon gas at a flow rate of 60 to 100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the C target, set the arc current to 60A~100A, the bias voltage to 100V~300V, and the deposition thickness to 100-500nm.
[0024] In one embodiment, the specific process of depositing the PECVD layer on the AIP layer in step (5) is as follows: introducing argon gas at a flow rate of 20 to 80 sccm, introducing acetylene gas at a flow rate of 100 to 200 sccm, maintaining the vacuum degree at 0.3 to 3 Pa, setting the bias voltage at 100 to 500 V, turning on the filament power supply at the same time, setting the filament power supply voltage at 40 to 100 V, and the filament power supply DC at 2 to 10 A. The thickness of the PECVD layer is 800 to 1000 nm.
[0025] In summary, the technical solution proposed by the present invention has the following beneficial effects:
[0026] (1) The DLC coating prepared by the present invention has excellent interface bonding strength by providing a metal base layer and a carbon transition layer;
[0027] (2) The present invention prepares the DLC coating by composite method of AIP and PECVD, which has higher hardness and lower surface friction coefficient;
[0028] (3) The method of the present invention is simple to implement and can be directly implemented on existing multi-arc ion plating equipment through a process method without the need for complex modifications to the equipment. DETAILED DESCRIPTION
[0029] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present disclosure belongs. In the event of a conflict, the definitions in this specification shall prevail.
[0030] Unless otherwise indicated, all percentages, parts, ratios, etc. are by weight.
[0031] As used herein, the terms "comprises," "comprising," "having," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that includes a list of elements is not necessarily limited to only those elements but may also include other elements not expressly listed or inherent to the composition, process, method, article, or apparatus.
[0032] When quantity, weight parts or other numerical value or parameter are given with range, preferred range or a series of upper preferred value and lower preferred value, it should be understood that it specifically discloses all ranges formed by any pair of numerical values of any larger range limit or preferred value and any smaller range limit or preferred value, regardless of whether the range is disclosed respectively. For example, when describing the range of "1 to 5", the described range should be understood to include the range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. Unless otherwise stated, in the description of numerical range herein, the range is intended to include the range end value and all integers, fractions, decimals, etc. within the range.
[0033] In addition, the indefinite articles "a" and "an" before the elements or components of the present disclosure are intended to indicate that the number of occurrences (i.e., occurrences) of the elements or components is not limited. Therefore, "a" or "an" should be understood to include one or at least one, unless it is clearly indicated that the number is singular, otherwise the elements or components in the singular form also include the plural case.
[0034] Unless specifically stated, the materials, methods, and examples described herein are illustrative only and not limiting. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present disclosure, suitable methods and materials are still described herein.
[0035] The present disclosure is described in detail below.
[0036] Specifically, the first aspect of the present invention provides a method for preparing a DLC coating with high interface strength, the method comprising the following steps:
[0037] (1) Polishing and cleaning of substrate surface;
[0038] (2) substrate heating and decontamination;
[0039] (3) depositing a metal primer layer on the surface of the substrate, and depositing a carbon transition layer on the metal primer layer;
[0040] (4) depositing an AIP layer on the carbon transition layer;
[0041] (5) depositing a PECVD layer on the AIP layer;
[0042] (6) Cooling to obtain a DLC coating with high interface strength.
[0043] The above preparation process can also be summarized as the following process steps: substrate pretreatment → furnace vacuuming → heating → filament cleaning → interface strengthening layer coating → AIP layer coating → PECVD layer coating → furnace cooling → furnace unloading.
[0044] Among them, step (1) in the method is the substrate pretreatment in the process steps; step (2) in the method is the vacuuming, heating and filament cleaning in the process steps; step (3) in the method is the interface strengthening layer plating in the process steps; step (4) in the method is the AIP layer plating in the process steps; step (5) in the method is the PECVD layer plating in the process steps; step (6) in the method is cooling with the furnace and taking out of the furnace.
[0045] The present invention unexpectedly discovered that the method of the present invention can effectively solve the problems of insufficient hardness and wear resistance of DLC coatings prepared by the existing PECVD method, as well as the problems existing in the traditional technical method of preparing DLC by multi-arc ion plating (AIP), while maintaining the advantages of the DLC coating having a dense surface structure and high lubricity.
[0046] The specific process of polishing and cleaning the substrate surface in step (1) is as follows: polishing the substrate surface to a mirror surface, and then ultrasonically cleaning it with acetone and anhydrous ethanol in sequence.
[0047] The specific process of heating and decontamination of the substrate in step (2) is as follows: -2 ~7×10 -2 Pa, the temperature was 100-150℃, argon gas was introduced at a flow rate of 60-100 sccm, and the vacuum degree was maintained at 3×10 -2 ~5×10 - 2 Pa, set the bias voltage between 50 and 900 V, increase gradually or in steps, clean and decontaminate.
[0048] In step (2), the surface of the substrate is fully etched by Ar ions to remove rust, stains and dust on the surface of the substrate, thereby ensuring that the interface strengthening layer can be firmly connected to the substrate, improving the bonding strength of the coating, preventing the coating from falling off and cracking, and thus increasing the life of the coating.
[0049] The specific process of depositing a metal base layer on the substrate surface in step (3) is as follows:
[0050] S1. Introduce argon gas at a flow rate of 60 to 100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the Cr target, set the arc current to 60A-100A, the bias voltage to 400V-900V, and the deposition thickness to 30-50nm;
[0051] S2. The vacuum is maintained at 3×10 -2 ~5×10 -2Pa, open the Cr target, set the arc current to 60A-150A, the bias voltage to 40V-400V, and the deposition thickness to 300-800nm;
[0052] S3. Introduce argon gas at a flow rate of 60 to 100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the Cr target, set the arc current to 60A~100A, the bias voltage to 400V~900V, and the deposition thickness to 30~50nm.
[0053] The specific process of depositing a carbon transition layer on the metal base layer in step (3) is as follows:
[0054] S4. Introduce argon gas at a flow rate of 60 to 100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, turn on the C target, set the arc current to 60A~100A, the bias voltage to 300V~900V, and the deposition thickness to 30~50nm.
[0055] In step (3) of the present invention, a metal primer layer is formed on the surface of the substrate by a metal Cr target, providing a suitable surface for the DLC coating, ensuring that the coating can be firmly attached to the substrate, and improving the hardness, wear resistance, corrosion resistance and mechanical strength of the coating. Subsequently, the C target is deposited under a relatively high negative bias voltage to form a transition layer with a high Sp3 (diamond phase) content. At the same time, the high bias voltage makes the ionized C ions have a higher energy, so that the carbon particles diffuse more fully during the film deposition, which reduces the appearance of micropores to a certain extent, makes the film denser, and obtains a smaller surface roughness, thereby forming a high-density, high-hardness DLC transition layer with good bonding force.
[0056] The specific process of depositing the AIP layer on the carbon transition layer in step (4) is as follows:
[0057] S5. Introduce argon gas at a flow rate of 60 to 100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the C target, set the arc current to 60A-100A, the bias voltage to 200V-400V, and the deposition thickness to 100-500nm;
[0058] S6. Introduce argon gas at a flow rate of 60 to 100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the C target, set the arc current to 60A~100A, the bias voltage to 100V~300V, and the deposition thickness to 100-500nm.
[0059] In step (4) of the present invention, after the carbon transition layer is formed, the bias voltage of the C target deposition is appropriately reduced. On the one hand, it is to prevent the high-energy C ion deposition time from being too long, causing etching damage to the formed film. On the other hand, reducing the bias voltage can effectively reduce the internal stress of the coating. At the same time, the bias deposition condition can also ensure that the Sp3 content of the coating is sufficient, thereby ensuring the high hardness and wear resistance of the coating.
[0060] The specific process of depositing the PECVD layer on the AIP layer in step (5) is as follows: introducing argon gas at a flow rate of 20 to 80 sccm, introducing acetylene gas at a flow rate of 100 to 200 sccm, maintaining the vacuum degree at 0.3 to 3 Pa, setting the bias voltage at 100 to 500 V, turning on the filament power supply at the same time, setting the filament power supply voltage at 40 to 100 V, and the filament power supply DC at 2 to 10 A. The thickness of this PECVD layer is 800 to 1000 nm.
[0061] Example 1
[0062] A method for preparing a DLC coating with high interface strength, the method comprising the following steps:
[0063] (1) A high-speed steel with a size of 20 mm × 5 mm was selected as the substrate. Before the test, the substrate surface was ground with sandpaper, and then the substrate surface was polished to a mirror surface with a diamond polishing paste with a grain size of 2.5 μm. Before entering the furnace, the substrate sample was ultrasonically cleaned with acetone for 30 minutes, then ultrasonically cleaned with anhydrous ethanol for 30 minutes, and finally dried with cold air;
[0064] (2) Open the mechanical pump and rough pumping valve to roughly pump the chamber, and at the same time open the molecular pump to accelerate, close the gate valve, and when the vacuum degree reaches 2.9 Pa, open the fore valve and gate valve to finely pump; when the vacuum degree reaches 2×10 -2 Pa, turn on the heater, set the output power to 100%, and heat to 100°C; introduce argon gas at a flow rate of 60 sccm and maintain the vacuum degree at 3×10 - 2 Pa, turn on the filament power supply, set the bias voltage to 50V, increase gradually or in steps, and the cleaning time is 30min;
[0065] (3) A metal base layer is deposited on the surface of the substrate, and a carbon transition layer is deposited on the metal base layer. The specific process is as follows:
[0066] S1. Introduce argon gas at a flow rate of 60 sccm and maintain the vacuum degree at 3×10 -2 Pa, turn on the Cr target, set the arc current to 60A, the bias voltage to 400V, and the deposition thickness to 30nm;
[0067] S2. The vacuum is maintained at 3×10 -2 Pa, turn on the Cr target, set the arc current to 60A, the bias voltage to 40V, and the deposition thickness to 300nm;
[0068] S3. Introduce argon gas at a flow rate of 60 sccm and maintain the vacuum degree at 3×10 -2 Pa, turn on the Cr target, set the arc current to 60A, the bias voltage to 400V, and the deposition thickness to 30nm;
[0069] S4. Introduce argon gas at a flow rate of 60 sccm and maintain the vacuum degree at 3×10 -2 Pa, turn on the C target, set the arc current to 60A, the bias voltage to 300V, and the deposition thickness to 30nm;
[0070] (4) Depositing the AIP layer on the carbon transition layer, the specific process is as follows:
[0071] S5. Introduce argon gas at a flow rate of 60 sccm and maintain the vacuum degree at 3×10 -2 Pa, turn on the C target, set the arc current to 60A, the bias voltage to 150V, and the deposition thickness to 100nm;
[0072] S6. Introduce argon gas at a flow rate of 60 sccm and maintain the vacuum degree at 3×10 -2 Pa, open the C target, set the arc current to 60A, the bias voltage to 50V, and the thickness of the bonding layer to 100nm;
[0073] (5) introducing argon gas at a flow rate of 20 sccm and acetylene gas at a flow rate of 100 sccm, maintaining the vacuum degree at 0.3 Pa, setting the bias voltage at 100 V, turning on the filament power supply at the same time, setting the filament power supply voltage at 40 V, and the filament power supply DC at 2 A. The deposition thickness of this PECVD layer is 800 nm;
[0074] (6) Turn off all heaters and allow natural cooling. When the temperature reaches below 60°C, remove the tube from the air.
[0075] Example 2
[0076] A method for preparing a DLC coating with high interface strength, the method comprising the following steps:
[0077] (1) A high-speed steel with a size of 20 mm × 5 mm was selected as the substrate. Before the test, the substrate surface was ground with sandpaper, and then the substrate surface was polished to a mirror surface with a diamond polishing paste with a grain size of 2.5 μm. Before entering the furnace, the substrate sample was ultrasonically cleaned with acetone for 30 minutes, then ultrasonically cleaned with anhydrous ethanol for 30 minutes, and finally dried with cold air;
[0078] (2) Open the mechanical pump and rough pumping valve to roughly pump the chamber, and at the same time open the molecular pump to accelerate, close the gate valve, and when the vacuum reaches 2.9 Pa, open the fore valve and gate valve to fine pump; when the vacuum reaches 4×10 -2 Pa, turn on the heater, set the output power to 100%, and heat to 130°C; introduce argon gas at a flow rate of 80 sccm to maintain the vacuum degree at 3.7×10 -2 Pa, turn on the filament power supply, set the bias voltage to 300V, increase gradually or in steps, and the cleaning time is 30min;
[0079] (3) A metal base layer is deposited on the surface of the substrate, and a carbon transition layer is deposited on the metal base layer. The specific process is as follows:
[0080] S1. Introduce argon gas at a flow rate of 70 sccm and maintain the vacuum degree at 3.8×10 -2 Pa, turn on the Cr target, set the arc current to 70A, the bias voltage to 500V, and the deposition thickness to 37nm;
[0081] S2. Argon gas with a flow rate of 120 sccm was used to maintain the vacuum degree at 3.9×10 -2 Pa, turn on the Cr target, set the arc current to 82A, the bias voltage to 270V, and the deposition thickness to 480nm;
[0082] S3. Introduce argon gas at a flow rate of 70 sccm and maintain the vacuum degree at 3.7×10 -2 Pa, turn on the Cr target, set the arc current to 70A, the bias voltage to 500V, and the deposition thickness to 36nm;
[0083] S4. Introduce argon gas at a flow rate of 78 sccm and maintain the vacuum degree at 3.8×10 -2 Pa, turn on the C target, set the arc current to 70A, the bias voltage to 500V, and the deposition thickness to 38nm;
[0084] (4) Depositing the AIP layer on the carbon transition layer, the specific process is as follows:
[0085] S5. Introduce argon gas at a flow rate of 70 sccm and maintain the vacuum degree at 3.9×10 -2 Pa, turn on the C target, set the arc current to 70A, the bias voltage to 180V, and the deposition thickness to 260nm;
[0086] S6. Introduce argon gas at a flow rate of 75 sccm and maintain the vacuum degree at 3.9×10 -2 Pa, open the C target, set the arc current to 70A, the bias voltage to 130V, and the thickness of the bonding layer to 300nm;
[0087] (5) introducing argon gas at a flow rate of 40 sccm and acetylene gas at a flow rate of 130 sccm, maintaining the vacuum degree at 1.8 Pa, setting the bias voltage at 220 V, turning on the filament power supply at the same time, setting the filament power supply voltage at 60 V, and the filament power supply DC at 4 A. The deposition thickness of this PECVD layer is 870 nm;
[0088] (6) Turn off all heaters and allow natural cooling. When the temperature reaches below 60°C, remove the tube from the air.
[0089] Example 3
[0090] A method for preparing a DLC coating with high interface strength, the method comprising the following steps:
[0091] (1) A high-speed steel with a size of 20 mm × 5 mm was selected as the substrate. Before the test, the substrate surface was ground with sandpaper, and then the substrate surface was polished to a mirror surface with a diamond polishing paste with a grain size of 2.5 μm. Before entering the furnace, the substrate sample was ultrasonically cleaned with acetone for 30 minutes, then ultrasonically cleaned with anhydrous ethanol for 30 minutes, and finally dried with cold air;
[0092] (2) Open the mechanical pump and rough pumping valve to roughly pump the chamber, and at the same time open the molecular pump to accelerate, close the gate valve, and when the vacuum degree reaches 2.9 Pa, open the fore valve and gate valve to finely pump; when the vacuum degree reaches 6×10 -2 Pa, turn on the heater, set the output power to 100%, and heat to 140°C; introduce argon gas at a flow rate of 90 sccm to maintain the vacuum degree at 4.7×10 -2 Pa, turn on the filament power supply, set the bias voltage to 760V, increase gradually or in steps, and the cleaning time is 30min;
[0093] (3) A metal base layer is deposited on the surface of the substrate, and a carbon transition layer is deposited on the metal base layer. The specific process is as follows:
[0094] S1. Introduce argon gas at a flow rate of 90 sccm and maintain the vacuum degree at 4.3×10 -2 Pa, turn on the Cr target, set the arc current to 90A, the bias voltage to 790V, and the deposition thickness to 40nm;
[0095] S2. Argon gas with a flow rate of 180 sccm was used to maintain the vacuum degree at 4.3×10 -2 Pa, turn on the Cr target, set the arc current to 138A, the bias voltage to 327V, and the deposition thickness to 720nm;
[0096] S3. Introduce argon gas at a flow rate of 80 sccm and maintain the vacuum degree at 4.5×10 -2Pa, turn on the Cr target, set the arc current to 90A, the bias voltage to 820V, and the deposition thickness to 45nm;
[0097] S4. Introduce argon gas at a flow rate of 90 sccm and maintain the vacuum degree at 4.5×10 -2 Pa, turn on the C target, set the arc current to 90A, the bias voltage to 800V, and the deposition thickness to 43nm;
[0098] (4) Depositing the AIP layer on the carbon transition layer, the specific process is as follows:
[0099] S5. Introduce argon gas at a flow rate of 90 sccm and maintain the vacuum degree at 4×10 -2 Pa, turn on the C target, set the arc current to 80A, the bias voltage to 260V, and the deposition thickness to 400nm;
[0100] S6. Introduce argon gas at a flow rate of 90 sccm and maintain the vacuum degree at 4.3×10 -2 PPa, open the C target, set the arc current to 85A, the bias voltage to 190V, and the thickness of the bonding layer to 480nm;
[0101] (5) introducing argon gas at a flow rate of 70 sccm and acetylene gas at a flow rate of 180 sccm, maintaining the vacuum degree at 2.5 Pa, setting the bias voltage at 470 V, turning on the filament power supply at the same time, setting the filament power supply voltage at 90 V, and the filament power supply DC at 7 A. The deposition thickness of this PECVD layer is 900 nm;
[0102] (6) Turn off all heaters and allow natural cooling. When the temperature reaches below 60°C, remove the tube from the air.
[0103] Example 4
[0104] A method for preparing a DLC coating with high interface strength, the method comprising the following steps:
[0105] (1) A high-speed steel with a size of 20 mm × 5 mm was selected as the substrate. Before the test, the substrate surface was ground with sandpaper, and then the substrate surface was polished to a mirror surface with a diamond polishing paste with a grain size of 2.5 μm. Before entering the furnace, the substrate sample was ultrasonically cleaned with acetone for 30 minutes, then ultrasonically cleaned with anhydrous ethanol for 30 minutes, and finally dried with cold air;
[0106] (2) Open the mechanical pump and rough pumping valve to roughly pump the chamber, and at the same time open the molecular pump to accelerate, close the gate valve, and when the vacuum degree reaches 2.9 Pa, open the fore valve and gate valve to finely pump; when the vacuum degree reaches 7×10 -2 Pa, turn on the heater, set the output power to 100%, and heat to 150 °C; introduce argon gas at a flow rate of 100 sccm and maintain the vacuum degree at 5 × 10-2 Pa, turn on the filament power supply, set the bias voltage to 900V, increase gradually or in steps, and the cleaning time is 30min;
[0107] (3) A metal base layer is deposited on the surface of the substrate, and a carbon transition layer is deposited on the metal base layer. The specific process is as follows:
[0108] S1. Introduce argon gas at a flow rate of 100 sccm and maintain the vacuum degree at 5×10 -2 Pa, turn on the Cr target, set the arc current to 100 A, the bias voltage to 900 V, and the deposition thickness to 50 nm;
[0109] S2. Argon gas was passed through at a flow rate of 200 sccm to maintain the vacuum degree at 5×10 -2 Pa, turn on the Cr target, set the arc current to 150A, the bias voltage to 400V, and the deposition thickness to 800nm;
[0110] S3. Introduce argon gas at a flow rate of 100 sccm and maintain the vacuum degree at 5×10 -2 Pa, turn on the Cr target, set the arc current to 100 A, the bias voltage to 900 V, and the deposition thickness to 50 nm;
[0111] S4. Introduce argon gas at a flow rate of 100 sccm and maintain the vacuum degree at 5×10 -2 Pa, turn on the C target, set the arc current to 100A, the bias voltage to 900V, and the deposition thickness to 50nm;
[0112] (4) Depositing the AIP layer on the carbon transition layer, the specific process is as follows:
[0113] S5. Introduce argon gas at a flow rate of 100 sccm and maintain the vacuum degree at 5×10 -2 Pa, turn on the C target, set the arc current to 100A, the bias voltage to 300V, and the deposition thickness to 500nm;
[0114] S6. Introduce argon gas at a flow rate of 100 sccm and maintain the vacuum degree at 5×10 -2 Pa, open the C target, set the arc current to 100A, the bias voltage to 200V, and the thickness of the bonding layer to 500nm;
[0115] (5) introducing argon gas at a flow rate of 80 sccm and acetylene gas at a flow rate of 200 sccm, maintaining the vacuum degree at 3 Pa, setting the bias voltage at 500 V, turning on the filament power supply at the same time, setting the filament power supply voltage at 100 V, and the filament power supply DC at 10 A. The deposition thickness of this PECVD layer is 1000 nm;
[0116] (6) Turn off all heaters and allow natural cooling. When the temperature reaches below 60°C, remove the tube from the air.
[0117] Comparative Example 1
[0118] It is basically the same as Example 2, except that the metal primer layer in step (3) is missing.
[0119] Comparative Example 2
[0120] It is basically the same as Example 2, except that the carbon transition layer in step (3) is missing.
[0121] Comparative Example 3
[0122] It is basically the same as Example 2, except that step (3) is missing.
[0123] Comparative Example 4
[0124] It is basically the same as Example 2, except that step (4) is missing.
[0125] Comparative Example 5
[0126] A method for preparing a DLC coating with high interface strength, the method comprising the following steps:
[0127] (1) A high-speed steel with a size of 20 mm × 5 mm was selected as the substrate. Before the test, the substrate surface was ground with sandpaper, and then the substrate surface was polished to a mirror surface with a diamond polishing paste with a grain size of 2.5 μm. Before entering the furnace, the substrate sample was ultrasonically cleaned with acetone for 30 minutes, then ultrasonically cleaned with anhydrous ethanol for 30 minutes, and finally dried with cold air;
[0128] (2) Open the mechanical pump and rough pumping valve to roughly pump the chamber, and at the same time open the molecular pump to accelerate, close the gate valve, and when the vacuum degree reaches 2.9 Pa, open the fore valve and gate valve to finely pump; when the vacuum degree reaches 2×10 -2 Pa, turn on the heater, set the output power to 100%, and heat to 100°C; introduce argon gas at a flow rate of 60 sccm, and maintain the vacuum degree at 3×10 - 2 Pa, turn on the filament power supply, set the bias voltage to 20V, increase gradually or in steps, and the cleaning time is 30min;
[0129] (3) A metal base layer is deposited on the surface of the substrate, and a carbon transition layer is deposited on the metal base layer. The specific process is as follows:
[0130] S1. Introduce argon gas at a flow rate of 30 sccm and maintain the vacuum degree at 2×10 -2 Pa, turn on the Cr target, set the arc current to 50A, the bias voltage to 300V, and the deposition thickness to 20nm;
[0131] S2. Argon gas with a flow rate of 90 sccm was used to maintain the vacuum degree at 3×10 -2 Pa, turn on the Cr target, set the arc current to 50A, the bias voltage to 30V, and the deposition thickness to 250nm;
[0132] S3. Introduce argon gas at a flow rate of 50 sccm and maintain the vacuum degree at 2×10 -2 Pa, turn on the Cr target, set the arc current to 50A, the bias voltage to 300V, and the deposition thickness to 25nm;
[0133] S4. Introduce argon gas at a flow rate of 40 sccm and maintain the vacuum degree at 2.5×10 -2 Pa, turn on the C target, set the arc current to 50A, the bias voltage to 255V, and the deposition thickness to 26nm;
[0134] (4) Depositing the AIP layer on the carbon transition layer, the specific process is as follows:
[0135] S5. Introduce argon gas at a flow rate of 50 sccm and maintain the vacuum degree at 2.3×10 -2 Pa, turn on the C target, set the arc current to 50A, the bias voltage to 120V, and the deposition thickness to 90nm;
[0136] S6. Introduce argon gas at a flow rate of 50 sccm and maintain the vacuum degree at 2.5×10 -2 PPa, open the C target, set the arc current to 50A, the bias voltage to 40V, and the thickness of the bonding layer to 90nm;
[0137] (5) introducing argon gas at a flow rate of 15 sccm and acetylene gas at a flow rate of 90 sccm, maintaining the vacuum degree at 0.2 Pa, setting the bias voltage at 90 V, turning on the filament power supply at the same time, setting the filament power supply voltage at 30 V, and the filament power supply DC at 1.6 A. The deposition thickness of this PECVD layer is 700 nm;
[0138] (6) Turn off all heaters and allow natural cooling. When the temperature reaches below 60°C, remove the tube from the air.
[0139] Comparative Example 6
[0140] A method for preparing a DLC coating with high interface strength, the method comprising the following steps:
[0141] (1) A high-speed steel with a size of 20 mm × 5 mm was selected as the substrate. Before the test, the substrate surface was ground with sandpaper, and then the substrate surface was polished to a mirror surface with a diamond polishing paste with a grain size of 2.5 μm. Before entering the furnace, the substrate sample was ultrasonically cleaned with acetone for 30 minutes, then ultrasonically cleaned with anhydrous ethanol for 30 minutes, and finally dried with cold air;
[0142] (2) Open the mechanical pump and rough pumping valve to roughly pump the chamber, and at the same time open the molecular pump to accelerate, close the gate valve, and when the vacuum degree reaches 2.9 Pa, open the fore valve and gate valve to finely pump; when the vacuum degree reaches 7.3×10 -2 Pa, turn on the heater, set the output power to 100%, and heat to 153 °C; introduce argon gas at a flow rate of 102 sccm to maintain the vacuum degree at 5.3×10 -2 Pa, turn on the filament power supply, set the bias voltage to 914V, increase gradually or in steps, and the cleaning time is 30min;
[0143] (3) A metal base layer is deposited on the surface of the substrate, and a carbon transition layer is deposited on the metal base layer. The specific process is as follows:
[0144] S1. Introduce argon gas at a flow rate of 100 sccm and maintain the vacuum degree at 5.5×10 -2 Pa, turn on the Cr target, set the arc current to 105A, the bias voltage to 909V, and the deposition thickness to 52nm;
[0145] S2. Argon gas with a flow rate of 211 sccm was used to maintain the vacuum degree at 5.5×10 -2 Pa, turn on the Cr target, set the arc current to 157A, the bias voltage to 411V, and the deposition thickness to 811nm;
[0146] S3. Introduce argon gas at a flow rate of 103 sccm and maintain the vacuum degree at 5.3×10 -2 Pa, turn on the Cr target, set the arc current to 102A, the bias voltage to 914V, and the deposition thickness to 53nm;
[0147] S4. Introduce argon gas at a flow rate of 110 sccm and maintain the vacuum degree at 5.4×10 -2 Pa, turn on the C target, set the arc current to 108A, the bias voltage to 910V, and the deposition thickness to 55nm.
[0148] (4) Depositing the AIP layer on the carbon transition layer, the specific process is as follows:
[0149] S5. Introduce argon gas at a flow rate of 110 sccm and maintain the vacuum degree at 5.5×10 -2 Pa, turn on the C target, set the arc current to 105A, the bias voltage to 309V, and the deposition thickness to 510nm;
[0150] S6. Introduce argon gas at a flow rate of 118 sccm and maintain the vacuum degree at 5.5×10 -2 Pa, open the C target, set the arc current to 128A, the bias voltage to 278V, and the thickness of the bonding layer to 553nm;
[0151] (5) introducing argon gas at a flow rate of 85 sccm and acetylene gas at a flow rate of 290 sccm, maintaining the vacuum degree at 3.5 Pa, setting the bias voltage at 525 V, turning on the filament power supply at the same time, setting the filament power supply voltage at 120 V, and the filament power supply DC at 12 A. The deposition thickness of this PECVD layer is 1100 nm;
[0152] (6) Turn off all heaters and allow natural cooling. When the temperature reaches below 60°C, remove the tube from the air.
[0153] Detection:
[0154] Examples 1 to 4 and Comparative Examples 1 to 6 were tested as follows:
[0155] Interface bonding strength: The scratch test was performed using the MFT-4000 multifunctional material surface performance tester; standard: "JB / T 8554-1997 Scratch test method for adhesion between vapor deposited films and substrates".
[0156] Hardness: Digital micro Vickers hardness tester.
[0157] Surface friction coefficient: The friction and wear test was carried out using the MFT-4000 multifunctional material surface performance tester, and the friction pair ball was made of ZrO2.
[0158] In the case of very poor interface bonding, the hardness and surface friction coefficient cannot be detected, and the result is: not detected.
[0159] The test results are shown in the following table:
[0160] Interface bonding strength / N Surface friction coefficient Hardness / HV Example 1 98 0.15 6097 Example 2 132 0.04 11230 Example 3 124 0.08 10095 Example 4 106 0.11 9560 Comparative Example 1 40 0.43 2598 Comparative Example 2 20 0.43 2598 Comparative Example 3 8 Not Detected Not Detected Comparative Example 4 33 0.56 2165 Comparative Example 5 76 0.33 5382 Comparative Example 6 82 0.23 5648
[0161] In summary, the DLC coating prepared by the present invention has excellent interface bonding strength, high hardness and low surface friction coefficient;
[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a DLC coating with high interface strength, characterized in that: The method comprises the following steps: (1) Polishing and cleaning of substrate surface; (2) Heating and decontamination of substrate; (3) depositing a metal base layer on the surface of the substrate, and depositing a carbon transition layer on the metal base layer; (4) depositing an AIP layer on the carbon transition layer; (5) Depositing a PECVD layer on the AIP layer; (6) Cooling to obtain a DLC coating with high interface strength.
2. The method for preparing a DLC coating with high interface strength according to claim 1, characterized in that: The specific process of step (1) is: polishing the surface of the substrate to a mirror surface, and then ultrasonically cleaning it with acetone and anhydrous ethanol in sequence.
3. The method for preparing a DLC coating with high interface strength according to claim 1, characterized in that: The specific process of step (2) is as follows: at a vacuum degree of 2×10 -2 ~7×10 -2 Pa, the temperature was 100~150℃, argon gas was introduced at a flow rate of 60~100sccm, and the vacuum degree was maintained at 3×10 -2 ~5×10 -2 Pa, set the bias voltage at 50~900V, clean and decontaminate.
4. The method for preparing a DLC coating with high interface strength according to claim 1, characterized in that: The specific process of depositing a metal base layer on the substrate surface in step (3) is as follows: S1. Introduce argon gas at a flow rate of 60~100sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the Cr target, set the arc current to 60A~100A, the bias voltage to 400V~900V, and the deposition thickness to 30~50nm; S2. The vacuum is maintained at 3×10 -2 ~5×10 -2 Pa, open the Cr target, set the arc current to 60A~150A, the bias voltage to 40V~400V, and the deposition thickness to 300~800nm; S3. Introduce argon gas at a flow rate of 60-100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the Cr target, set the arc current to 60A~100A, the bias voltage to 400V~900V, and the deposition thickness to 30~50nm.
5. The method for preparing a DLC coating with high interface strength according to claim 4, characterized in that: The specific process of depositing the carbon transition layer on the metal base layer in step (3) is as follows: S4. Introduce argon gas at a flow rate of 60-100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the C target, set the arc current to 60A~100A, the bias voltage to 300V~900V, and the deposition thickness to 30~50nm.
6. The method for preparing a DLC coating with high interface strength according to claim 5, characterized in that: The specific process of depositing the AIP layer on the carbon transition layer in step (4) is as follows: S5. Introduce argon gas at a flow rate of 60-100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the C target, set the arc current to 60A~100A, the bias voltage to 200V~400V, and the deposition thickness to 100~500nm; S6. Introduce argon gas at a flow rate of 60-100 sccm and maintain the vacuum degree at 3×10 -2 ~5×10 -2 Pa, open the C target, set the arc current to 60A~100A, the bias voltage to 100V~300V, and the deposition thickness to 100-500nm.
7. The method for preparing a DLC coating with high interface strength according to claim 5, characterized in that: The specific process of depositing the PECVD layer on the AIP layer in step (5) is as follows: introducing argon gas at a flow rate of 20-80 sccm, introducing acetylene gas at a flow rate of 100-200 sccm, maintaining the vacuum degree at 0.3-3 Pa, setting the bias voltage at 100-500 V, turning on the filament power supply at the same time, setting the filament power supply voltage at 40-100 V, and the filament power supply DC at 2-10 A. The thickness of the PECVD layer is 800-1000 nm.